57Fe-Mössbauer analysis of biological and synthetic Fe/S clusters - Hwang, Jaeeun; Han, Jaehong (Food Agricultural Sciences and Technology, 2015)
Biological Fe/S clusters play various important roles, such as electron transfer and substrate transformation. In the study of the electronic properties of biological and chemical Fe/S clusters, 57Fe-Mössbauer spectroscopy provides imperative information. In this review, practical aspects of 57Fe-Mössbauer spectroscopy,with an emphasis on the isomer shift δ,were discussed. The isomer shift values of the various biological Fe/S proteins and the synthetic Fe/S complexes at different oxidation states and electronic spin states, along with the related Mo/Fe/S and Fe carbonyl clusters, were reviewed. From the Mössbauer isomer shift, the physical properties of the Fe center in the Fe-enzymes can be obtained. In addition, the binding of the substrate or inhibitor to the active Fe center can be monitored.